The role of selective serotonin re-uptake inhibitors in themanagement of premature ejaculation - I. Abass Al-Janabi, Yasir (Tikrit Journal of Pharmaceutical Sciences, 2023)
A prospective, randomized, placebo-conlrolled study was designed to investigate the efticacy and side effects of the selective serotonin re-uptake inhibitor, fluoxetine hydrochloride, on postponing ejaculation in patients with premature ejaculation (PE). A total of 55 men with PE were scheduled to begin this study, but 5 of them have been dropped out for unknown reason, so tbc study was completed with a total number of 50 patients. The ages of these patients (who experienced primary premature ejaculation (lifelong rapid ejaculation)) ranging between 19 to 65 years. The patients were asked to detennine the time in seconds between vaginal penet.ration and ejaculation (latency time), by using a clock for four weeks before starting the trcatment,and a baseline mean ejaculatory latency time was measured. Then the patients were given either flouxetine hydrochloride or placebo for aditiomal 8 weeks. All patients were interviewed before and 8 weeks after beginning the treatment.Baseline mean ejaculatory latency time was 60.6 s; 20 mg/day of lluoxetine increased it to 199.3 s, while in patient using placebo it was 68. 15 s (p < 0.001). This resulted in significantly greater sexual satisfaction for men: 73% (p < 0.001). Generally. fluoxetine was well tolerated and there were no major side effects. None of the patients discontinued thempy due to adverse effects. Fluoxetinae hydrochloride may be regarded as a safe and effective option in the treatment of premature ejaculation.